2018
DOI: 10.5114/aoms.2016.60663
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age, sex, blepharitis, rosacea and rheumatoid arthritis on Demodex mite infection

Abstract: IntroductionTwo human-specific Demodex species have been described: Demodex folliculorum and Demodex brevis. A medical condition caused by the presence of Demodex is called demodicosis.Material and methodsThe study material comprised eyelashes collected from 1499 patients.Results Demodex sp. infection was revealed in 47% of patients (487 women and 216 men). We determined the following rates of infection by age groups: 1–25 (8% of infected subjects), 26–40 (36%), 41–55 (50%), 56–70 (67%), over 70 (77%). The sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 20 publications
2
37
0
1
Order By: Relevance
“…Regarding efficacy of antiparasitic effects, 100% D+ patients at baseline (16/50, 32%) turned negative after 16 weeks, proving the efficacy of ivermectin 1% cream in reducing Demodex density. In our study, according to the literature, the risk of Demodex infestation grows with age (average of D+ patient, 59 years old vs 54 years old in D– patients), but we did not find any significant differences (Lee, Chun, Kim, Kim, & Kim, ; Sędzikowska, Osęka, & Skopiński, ). Concerning the type of lesions, 87.5% of D+ patients presented a combination of erythema and papulopustules.…”
Section: Discussionsupporting
confidence: 55%
“…Regarding efficacy of antiparasitic effects, 100% D+ patients at baseline (16/50, 32%) turned negative after 16 weeks, proving the efficacy of ivermectin 1% cream in reducing Demodex density. In our study, according to the literature, the risk of Demodex infestation grows with age (average of D+ patient, 59 years old vs 54 years old in D– patients), but we did not find any significant differences (Lee, Chun, Kim, Kim, & Kim, ; Sędzikowska, Osęka, & Skopiński, ). Concerning the type of lesions, 87.5% of D+ patients presented a combination of erythema and papulopustules.…”
Section: Discussionsupporting
confidence: 55%
“…In turn, Sedzikowska et al examined 134 patients with blepharitis and 76% had positive result for Demodex . The authors also found that the sex of the subjects was not a factor conducive to infection, but their age was positively correlated with the risk of infection [ 25 ]. In our study, the result was very similar, as 72% of the patients with blepharitis had positive result for the presence of Demodex but there was no significant relationship of the Demodex infestation with age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Lower incidence of Demodex spp. infection was found by Sędzikowska et al [28] in patients of hospitals in Warsaw (47%). Wesołowska et al [22] determined the prevalence of infection of Demodex spp.…”
Section: Discussionmentioning
confidence: 88%